Improving Students' Ability to Write Simple and Compound Sentences in Personal Letters through the Contextual Teaching and Learning (CTL) Model - Dwi Setiawan; Dwi Rohman Soleh; Herman Trisna (Jurnal Pendidikan Edutama, 2026)
This study was motivated by the low ability of seventh-grade students at SMP Negeri 3 Madiun to write simple and compound sentences in personal letters. The study aimed to describe the improvement in this ability through the implementation of the Contextual Teaching and Learning (CTL) model. The study employed a Classroom Action Research (CAR) design based on the Kemmis and McTaggart model, conducted in two cycles with 30 students as the participants. Data were collected through written tests, classroom observations, and documentation, including students' writing products and photographs of classroom activities, and were analyzed using quantitative and qualitative approaches. The results showed that the class mean score increased from 58.3 in the pre-cycle to 70.5 in Cycle I and 82.4 in Cycle II. The percentage of learning mastery also increased from 30% in the pre-cycle to 56.7% in Cycle I and 86.7% in Cycle II. These findings indicate that the CTL model is effective in improving students' ability to write simple and compound sentences in personal letters.